A toolkit for rapid CRISPR-SpCas9 assisted construction of hexose-transport-deficient Saccharomyces cerevisiae strains. Issue 1 (3rd October 2018) - Wijsman, Melanie; Świat, Michał A; Marques, Wesley L; Hettinga, Johanna K; van den Broek, Marcel; Torre Cortés, Pilar de la; Mans, Robert; Pronk, Jack T; Daran, Jean-Marc; Daran-Lapujade, Pascale
Abstract: Hexose transporter-deficient yeast strains are valuable testbeds for the study of sugar transport by native and heterologous transporters. In the popular Saccharomyces cerevisiae strain EBY.VW4000, deletion of 21 transporters completely abolished hexose transport. However, repeated use of the Lox P/Cre system in successive deletion rounds also resulted in major chromosomal rearrangements, gene loss and phenotypic changes. In the present study, CRISPR/ Sp Cas9 was used to delete the 21 hexose transporters in an S. cerevisiae strain from the CEN.PK family in only three deletion rounds, using 11 unique guide RNAs. Even upon prolonged cultivation, the resulting strain IMX1812 (CRISPR- Hxt 0 ) was unable to consume glucose, while its growth rate on maltose was the same as that of a strain equipped with a full set of hexose transporters. Karyotyping and whole-genome sequencing of the CRISPR- Hxt 0 strain with Illumina and Oxford Nanopore technologies did not reveal chromosomal rearrangements or other unintended mutations besides a few SNPs. This study provides a new, 'genetically unaltered' hexose transporter-deficient strain and supplies a CRISPR toolkit for removing all hexose transporter genes from most S. cerevisiae laboratory strains in only three transformation rounds. Abstract : This study supplies a CRISPR-based toolkit enabling the simple, fast and precise deletion of 21 hexose-transporter genes in Saccharomyces cerevisiae laboratory strains and thereby the construction of hexose-transport deficient strains.